Choosing as a Freelancer: What should Gen Z prepare for? - Putri, Dian; Arifianto, Chandra (Journal Economic Business Innovation, 2024)
Purpose: This study aims to explore the factors influencing Generation Z’s decision to pursue a career as freelancers, particularly focusing on student workers. The research seeks to understand the reasons behind their career choices and assess their readiness for freelancing as a career path.Method: The study employs a descriptive quantitative research design, utilizing a survey method. The population consists of 45 respondents working as freelancers at PT Melia Sehat Sejahtera in Jakarta. Data collection was conducted through a questionnaire adapted from the Career Decision-Making Difficulties Questionnaire (CDDQ). The data were analyzed using simple calculations with Likert scoring.Findings: The results indicate that Generation Z prioritizes immediacy in their career decisions, viewing freelancing as a practical solution to current challenges and a personal choice aligned with their individual needs and preferences. The findings highlight the importance of flexibility and independence in their career readiness.Novelty: This study contributes to the limited literature on Generation Z’s career choices, particularly in freelancing, by providing empirical insights into the motivations and readiness of student workers entering the freelance market.Implications: The results have implications for career development programs and policy-makers, offering valuable information for creating strategies that support Generation Z in their transition to freelance careers. Understanding these factors is crucial for developing training and resources to enhance their career preparedness.